A novel solid self-emulsifying delivery system (SEDS) for the encapsulation of linseed oil and quercetin: Preparation and evaluation. (June 2018) - Huang, Juan; Wang, Qiang; Sun, Rui; Li, Tong; Xia, Nan; Xia, Qiang
Abstract: The aim of current research was to develop a solid self-emulsifying delivery system (SEDS) to enhance the delivery of linseed oil and quercetin. The pseudo ternary phase diagram was constructed to optimize the suitable liquid formulation. Liquid absorption on solid absorbent carrier was used to convert liquid into solid self-emulsifying lipid formulation by simple physical mixture. The solid carrier of Aerosil 300 showed highest adsorption capacity. Besides, the solid SEDS prepared with liquid formulation/Aerosil 300 ratio of 2:1 had good flow properties. FTIR indicated that linseed oil and quercetin were encapsulated in Aerosil 300. XRD study suggested that the crystalline structure of quercetin transformed to molecularly dissolved state in solid SEDS. In vitro digestion and release experiments showed that after solid adsorption, linseed oil and quercetin exhibited delayed release patterns. The accelerated oxidation study revealed that non aqueous system was more beneficial to the storage of linseed oil, and Aerosil 300 had no effect on the oxidation stability of linseed oil. Hence, solid SEDS is an attractive candidate for the encapsulation of functional oil and flavonoids for use in food industry. Highlights: Linseed oil and quercetin co-loaded self-emulsifying powders were fabricated. Aerosil 300 may inhibit the release of linseed oil. After absorbed by Aerosil 300, quercetin exhibited a delayed release pattern. Linseed oil in prepared powders was more stable than that in emulsions.